2014
DOI: 10.2134/jeq2012.0084
|View full text |Cite
|
Sign up to set email alerts
|

Application of Flue Gas Desulfurization Gypsum and Its Impact on Wheat Grain and Soil Chemistry

Abstract: The 11 major electricity-generating coal combustion stations in the northern Great Plains have the potential to produce almost 1 million Mg of flue gas desulfurization gypsum (FGDG) annually, which is a very attractive fertilizer (Ca and S) and amendment for sodic and acid soils. The potential environmental impacts of applying FGDG to soils in this region have not been fully investigated. The objectives of this research were to determine the influence of FGDG on soil chemical characteristics and to determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 30 publications
3
15
1
Order By: Relevance
“…Surface applying and deep banding gypsum to poorly-drained claypan soils in a conservation tillage system in Northeast Missouri did not consistently increase corn and soybean yields. This lack of response is contrary to some research that has found positive yield responses to applied gypsum or gypsum industrial byproducts (e.g., Chun et al, 2001;Chen et al, 2005,), but others have found no or inconsistent increases in agronomic yields (DeSutter et al, 2014;Kost et al, 2014). Lack of response to gypsum was most likely caused by the low levels of Al +3 in the surface soil and the limited effect of gypsum in altering the soil pH s .…”
Section: Discussioncontrasting
confidence: 65%
“…Surface applying and deep banding gypsum to poorly-drained claypan soils in a conservation tillage system in Northeast Missouri did not consistently increase corn and soybean yields. This lack of response is contrary to some research that has found positive yield responses to applied gypsum or gypsum industrial byproducts (e.g., Chun et al, 2001;Chen et al, 2005,), but others have found no or inconsistent increases in agronomic yields (DeSutter et al, 2014;Kost et al, 2014). Lack of response to gypsum was most likely caused by the low levels of Al +3 in the surface soil and the limited effect of gypsum in altering the soil pH s .…”
Section: Discussioncontrasting
confidence: 65%
“…Many experiments and studies on the effect and potentiality of FGDB as an amendment in agricultural applications have been conducted by various agencies and research institutes at dispersed locations all over the world [8][9][10][11][12]. Its use in agriculture is mainly based on its liming potential and supply of nutrients which promote growth of plants and alleviate the condition of nutrient deficiency in soils [13][14][15][16].…”
Section: Journal Of Chemistrymentioning
confidence: 99%
“…However, climatic conditions in this area are generally dryer than the eastern and southeastern regions of the United States, and impacts of agricultural FGD gypsum on crops and soils within the Great Plains have been limited. DeSutter et al (2014) applied FGD gypsum and commercial gypsum at rates of 0, 2.24, 11.2, and 22.4 Mg ha -1 to two acid soils (pH values 4.8 and 4.9) in southwestern North Dakota and evaluated soil, wheat yields, and grain chemistry during two growing seasons. Wheat grain yields and element analysis generally were not affected by gypsum.…”
Section: Agronomic Responses and Soil Physical Propertiesmentioning
confidence: 99%